2023
DOI: 10.1111/liv.15714
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial strain and ventricular global longitudinal strain in cirrhotic patients using the new criteria of Cirrhotic Cardiomyopathy Consortium

Marina Skouloudi,
Maria S. Bonou,
Magdalini Adamantou
et al.

Abstract: BackgroundThe new criteria of Cirrhotic Cardiomyopathy Consortium (CCC) propose the use of left ventricular global longitudinal strain (LV‐GLS) for evaluation of systolic function in patients with cirrhosis. The aim of this study was to evaluate LV‐GLS and left atrial (LA) strain in association with the severity of liver disease and to assess the characteristics of cirrhotic cardiomyopathy (CCM).MethodsOne hundred and thirty‐five cirrhotic patients were included. Standard echocardiography and speckle tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Skouloudi et al demonstrated that patients with MELD scores above 15 had significantly higher absolute GLS compared to patients with MELD scores below 15. This finding was also evident in the multivariate analysis, where the MELD score was the only factor associated with GLS [55]. Mechelink et al found that patients with decompensated LC had increased absolute GLS values compared to patients with compensated LC without portal hypertension.…”
Section: Are Left Ventricular Strain Values Associated With Disease S...mentioning
confidence: 67%
See 3 more Smart Citations
“…Skouloudi et al demonstrated that patients with MELD scores above 15 had significantly higher absolute GLS compared to patients with MELD scores below 15. This finding was also evident in the multivariate analysis, where the MELD score was the only factor associated with GLS [55]. Mechelink et al found that patients with decompensated LC had increased absolute GLS values compared to patients with compensated LC without portal hypertension.…”
Section: Are Left Ventricular Strain Values Associated With Disease S...mentioning
confidence: 67%
“…Skouloudi et al did not find an association between LA strain and MELD score. However, in the prospective study, they presented that patients with reduced LA reservoir strain had a worse prognosis in the multivariate model, which also included MELD (HR 0.96, 95%CI 0.93-0.99; p = 0.017) [55]. These initial findings are consistent in that LA strain does not differ so profoundly between patients and controls, as the left atrial dimension indicates.…”
Section: Speckle Tracking Echocardiography For the Evaluation Of Left...mentioning
confidence: 79%
See 2 more Smart Citations
“…Retrospective data suggest that diastolic dysfunction has a prevalence of 10.5-33.3% in patients with cirrhosis [ 20 , 46 ]. Diastolic dysfunction is characterized by a stiff ventricle with impaired relaxation and filling.…”
Section: Pathophysiologymentioning
confidence: 99%